(untitled) (Research, Society and Development, 2021)
Environmental Education (EA) is a reality implemented within schools through a public policy aimed at training and preparing citizens for critical reflection, but the current conservationist and pragmatic model implemented take into account the historical aspects and the economic model. without considering the social, political and cultural surroundings. There are several definitions of Environmental Education corresponding to the interests and do not necessarily take into consideration the relationship between man and environment.